2020
DOI: 10.1186/s12889-020-08744-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of occupational stress on depression and insomnia: a cross-sectional study among employees in a Ghanaian telecommunication company

Abstract: Background: Depression and insomnia are major psychiatric conditions predicted by occupational stress. However, the influence of occupational stress on these two conditions is under-explored in telecommunication companies, especially in Africa. This research was conducted to assess occupational stress in a Ghanaian telecommunication company and its effect on depression and insomnia. Methods: An analytical cross-sectional study was conducted among employees at a telecommunication company in Accra. Structured se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
(42 reference statements)
0
11
0
2
Order By: Relevance
“…The results obtained show a high prevalence of perceived stress (76.76%). In Ghana, Kploanyi et al (2020) reported a prevalence of occupational stress of 32.8% among the employees of telecommunications companies [ 10 ]. The high prevalence of workplace stress observed in the present study could be explained by the bad working environment conditions in the informal e-waste sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained show a high prevalence of perceived stress (76.76%). In Ghana, Kploanyi et al (2020) reported a prevalence of occupational stress of 32.8% among the employees of telecommunications companies [ 10 ]. The high prevalence of workplace stress observed in the present study could be explained by the bad working environment conditions in the informal e-waste sector.…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted in Ghana showed variable levels of stress and highlighted associations between exposure to adverse physical conditions and elevated heart rate among e-waste workers [ 9 ]. In the formal sector, it has been observed that occupational strain resulting from exposure to stressors in the workplace can affect the mental and physical health of employees [ 10 ]. Therefore, a study was conducted in five French-speaking West African countries to determine the prevalence and factors associated with perceived stress in the informal e-waste processing environment.…”
Section: Introductionmentioning
confidence: 99%
“…A study on a sample of telecommunication company employees and nurses showed that insomnia symptoms were related to alcohol use, with the highest insomnia levels being reported by high-risk drinkers, smokers, and individuals consuming more than three cups of coffee per day [141,142]. Structured interviews would also be a valuable addition.…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
“…The current work style and intensity of society will continue to increase the occurrence and development of occupational stress, and may even induce a variety of stress-related diseases. Occupational stress is associated with increased risk of mental disorders, [i.e., depression ( 2 ), burnout ( 3 )], somatic diseases [i.e., insomnia ( 4 ), hypertension ( 5 )], and organizational outcomes [i.e., job satisfaction ( 6 ), wellness ( 7 )]. In recent decades, occupational stress represents a large, complex and costly phenomenon in the workplace worldwide ( 8 ).…”
Section: Introductionmentioning
confidence: 99%